Correction Notice: Tools for Citizen-Science Recruitment and Student Engagement in Your Research and in Your Classroom (American Society for Microbiology, 2016)
Correction for Sarah E. Council and Julie E. Horvath, “Tools for Citizen-Science Recruitment and Student Engagement in Your Research and in Your Classroom,” which appeared in the Journal of Microbiology & Biology Education, volume 17, number 1, March 2016, pages 38–40.